PENGARUH PENYULUHAN GOOD HYGIENE PRACTICES (GHP) DENGAN MEDIA LEAFLET TERHADAP PERILAKU TENAGA PENJAMAH MAKANAN DI INSTALASI GIZI RSUD PROF.DR.H.M.CHATIB QUZWAIN KAB. SAROLANGUN TAHUN 2021 - Wilda Laila; Dezi Ilham; Yossy Octavia Manizar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research is motivated by the provision of food in hospitals, with the quality of service health standards and indications of patient disease so that food poisoning does not occur due to consuming food contaminated with microorganisms or their toxins. How to produce healthy food has been regulated in the Good Hygiene Practices (GHP) system. Therefore, food handlers must have good behavior regarding GHP. The purpose of this study was to determine the effect of Good Hygiene Practices (GHP) counseling with leaflet media on the behavior of food handlers at the Nutrition Installation of Prof. Hospital. DR. H.M. Chatib Quzwain Kab. Sarolangun 2021. The method used in this research is experimental (pre-experimental) with a one-group pre-test and post-test design. The population in this study were all food handlers at the Nutrition Installation of RSUD.PROF.DR. H. M. Chatib Quzwain Kab. Sarolangun with a sample of 14 people.The sampling technique is total sampling. The data collection instrument used a questionnaire sheet and a pretest and posttest check list form. Statistical analysis using t-dependent test. The study concluded that there were differences of the behavior of food handlers after being given counseling, which increased to high. In addition, there is an effect of providing counseling about GHP using leaflet media on the level of knowledge with a p-value of 0.0203, for attitudes with a p-value of 0.038 and on actions with a p-value of 0.0266. It is recommended to the Nutrition Installation of RSUD Prof. DR. H.M. Chatib Quzwain Kab. Sarolangun conducts periodic training on Good Hygiene Practices (GHP) with demonstration or role playing methods, improve the quality and quantity of both facilities and infrastructure to achieve good food security.